Childhood ADHD and Early-Onset Bipolar Disorder Comorbidity: A Case Report - Paraskevi Tatsiopoulou; Georgia-Nektaria Porfyri; Eleni Bonti; Ioannis Diakogiannis (Brain Sciences, 2020)
Introduction: Recent research has highlighted an increased rate of co-morbidity between the neurodevelopmental-behavioral disorder of attention deficit hyperactivity disorder (ADHD) and a variety of psychiatric disorders, such as mood disorders or bipolar disorder (BD). The etiology and clinical course of BD are considered to be determined by both genetic and environmental factors, either aggravating or improving. Aim: This follow-up study of an adolescent aimed to clarify the co-morbidity between ADHD and BD. We also discuss the controversies surrounding the two diagnoses in younger populations and describe several aspects of concern regarding diagnosis, differential diagnosis, therapeutic planning/intervention, and prognosis. Methods: Reporting of a two-year follow-up study of a bipolar 15-year-old female patient with a previous diagnosis of ADHD during childhood. Results: Despite the occurrence of major risk factors, such as early onset and positive family history, the patient’s condition rapidly remitted with medication, without relapse and/or rehospitalization during the following two years, due to the stability of her cooperation, and support of a stable and caring familial environment. Early diagnosis of BD and differential diagnoses of ADHD are considered crucial protective factors leading to an appropriate planning of treatment. In addition, parental involvement and empathic attitude towards the patient supported the latter to cooperate and comply with the treatment, enhancing positive outcomes and stability. Conclusions: Research is required into the reliability and validity of diagnostic protocols and criteria for BD in children and adolescents, and also into the development of individualized therapeutic planning.